Impact of climate and land use/land cover change on Lobo reservoir inflow, West-Central of Côte d'Ivoire - Bérenger Koffi; Alexis Loukou Brou; Kouamé Jean Olivier Kouadio; Valentin Brice Ebodé; Konan Jean-Yves N'guessan; Gnibga Issoufou Yangouliba; Konaté Yaya; Dibi Brou; Kouakou Lazare Kouassi (Journal of Hydrology: Regional Studies, 2023)
Study region: Lobo River Catchment (Côte d’Ivoire) Study focus: In this study, four regional climate models (RCMs) (RC4; CCLM4–8–17; RACMO22T and REMO) for the 2030 and 2050 periods compared to the reference period (1986–2005), combined with a simulation of land use and land cover (LULC) with Land Change Modeler, are used to drive the CEQUEAU model to quantify their impact on inflows to the Lobo River reservoir. 1988–2006 is used as a calibration period, whereas 2007–2015 is used for the validation. Three scenarios were used. First, varying LULC and keeping climate parameters static over the baseline period (scenario 1); in scenario 2, varying RCMs and keeping LULC static over the baseline period and in scenario 3, simultaneous variation of LULC and RCMs. New hydrological insights for the region: CEQUEAU showed good performance during calibration and validation: NSE (0.7, 0.75); R² (0.83, 0.65); PBIAS (14.1%, 12%) and RMSE (0.83, 2.15). The results show that a decrease in precipitation by 2030 (−14.6%), by 2050 (−15.2%) under scenario 2 (RCP 4.5 and 8.5) and by − 6.1% under RCP 4. 5 (Scenario 3), we observe an increase in runoff of 10.8–18.87% (Scenario 1), 1.2–4.46% (RCP4.5), 3.35% and 2.7% (RCP8.5) (Scenario 2) and 6.58–11.83 (RCP 4.5), 14.83–17.72% (RCP 8.5) (scenario 3). Changes in LULC were identified as the main causes, rather than climate variability.